1984
DOI: 10.1002/jsfa.2740351010
|View full text |Cite
|
Sign up to set email alerts
|

Composition and nutritive value of cormels of Colocasia esculenta (L.) Schott

Abstract: The nutritional quality of the cormels of Colocasia esculenta (L.) Schott cultivar 'Guavir' was determined chemically and biologically in feeding experiments with weanling rats. The contents of starch and unavailable carbohydrates (cellulose, hemicellulose and pectin) were 54 and 15% of the dry matter respectively. Lipid accounted for less than 1% of the dry matter. Palmitic, oleic and linoleic acids were the main fatty acids in the lipids, with linoleic acid predominating. The content and fatty acid compositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 19 publications
4
14
0
Order By: Relevance
“…The coefficient for age was negatively signed and significant at 5% probability level, this implies that increase in age will result in allocative inefficiency because most of the respondents were the aged and would tend to misallocate their resources. This was also reported by Idiong (2005) and Hussain et al (1984).…”
Section: (G) Estimation Of Allocative Efficiencysupporting
confidence: 85%
“…The coefficient for age was negatively signed and significant at 5% probability level, this implies that increase in age will result in allocative inefficiency because most of the respondents were the aged and would tend to misallocate their resources. This was also reported by Idiong (2005) and Hussain et al (1984).…”
Section: (G) Estimation Of Allocative Efficiencysupporting
confidence: 85%
“…The two values show that the flowers of the two cocoyam are protein rich. These results are in agreement with the report of Hussam et al [13] which reveals that the protein content of the corm of Xanthosoma sagittifolium (tannia) is significantly higher that the value of other tuber crops. Standal [14] also reported that Xanthosoma sagittifolium contains more amino acids than cassava, yam and sweet potatoes.…”
Section: Resultssupporting
confidence: 93%
“…Fractionation of the cell walls con®rmed this composition. In contrast, Hussain et al, 12 using dissimilar isolation and fractionation methods, obtained quite different results for the cell walls of taro cv Guavir grown in Bangladesh. They found that the walls contained 70% hemicellulose, 17% pectin and 13% cellulose by weight.…”
Section: Results and Discussion Histochemistrymentioning
confidence: 85%
“…11 However, another study, using selective extraction of polysaccharides, indicated that they contained 70% (w/w) hemicellulose polysaccharides. 12 The aims of the present study were to examine the cell wall composition of the raw corms of the taro cultivar Tausala Pink and to determine the effect of cooking on the composition.…”
Section: ±6mentioning
confidence: 99%